Chemical Reaction Effects on MHD Flow Past an Impulsively Started Isothermal Vertical Plate with Uniform Mass Diffusion - P. Chandrakala; P. Narayana Bhaskar (International Journal of Applied Mechanics and Engineering, 2014)
A numerical technique is employed to derive a solution to the transient natural convection flow of an incompressible viscous fluid past an impulsively started infinite isothermal vertical plate with uniform mass diffusion in the presence of a magnetic field and homogeneous chemical reaction of first order. The governing equations are solved using implicit finite-difference method. The effects of velocity, temperature and concentration for different parameters such as the magnetic field parameter, chemical reaction parameter, Prandtl number, Schmidt number, thermal Grashof number and mass Grashof number are studied. It is observed that the fluid velocity decreases with increasing the chemical reaction parameter and the magnetic field parameter.